Inhibition of Aspergillus parasiticus and detoxification of aflatoxin derivatives in tomato paste by adding freeze-dried postbiotic from Lactiplantibacillus plantarum - Tutuk, Zehra; Karatepe, Pinar; Akgol, Muzeyyen; Bayrak, Sinem; Vurmaz, Melike; Fidan, Serife; Incili, Gokhan Kursad (Elsevier Sci Ltd, 2026)
In this study, it was aimed to inhibit the Aspergillus parasiticus and detoxify the aflatoxin derivatives (B1, B2, G1, and G2) by adding the postbiotic of Lactiplantibacillus plantarum in tomato paste. The bioactive compounds in the postbiotic were also identified. The minimum inhibitory (MIC) and fungicidal concentrations (MFC) of the postbiotic were found to be 12.5 and 100 mg/mL against A. parasiticus, respectively. In addition, 10 mg of the postbiotic displayed a 16.47 mm inhibition zone. The postbiotics were added to the tomato pastes at 4, 6 and 8-fold of the MIC, and the physico-chemical, microbiological parameters, and the amount of aflatoxins were monitored during 45 days of storage at 4 degrees C. The number of A. parasiticus was found to be below the detection limit in the 8-fold concentration of the postbiotic-added tomato pastes on the 45th day (P < 0.05). Compared to untreated samples, this treatment also significantly reduced the populations of mesophilic aerobes, psychrotrophs, lactic acid bacteria, and anaerobes (P < 0.05). Importantly, the pH, color, and titratable acidity remained constant in all groups during storage (P > 0.05). In addition, the postbiotic significantly reduced the levels of aflatoxins B1, B2, G1 and G2 compared to the control in a dose-dependent manner (P < 0.05). The results revealed that the postbiotic contains various bioactive constituents, including organic, free fatty, and free amino acids, polyphenols and volatiles, and also has a strong antioxidant capacity. In conclusion, the addition of freeze-dried postbiotics to tomato paste shows strong antifungal and anti-aflatoxigenic effects without compromising physicochemical quality of the tomato paste.
Keywords: Tomato paste; Lactiplantibacillus plantarum; Postbiotic; Aspergillus parasiticus; Antifungal effect